PERUBAHAN PERILAKU KONSUMTIF MASYARAKAT DARI PASAR TRADISIONAL KE PASAR MODERN - IKA DEVY PRAMUDIANA (Asketik : Jurnal Agama dan Perubahan Sosial, 2017)
Along with the growth of advanced economies, especially in larger cities, there have been changes in varioussectors including industry and production and modern market. On the other hand there is a shift fromtraditional lifestyles into the modern, creating changes in consumer spending patterns. The purpose of thisstudy was to determine the impact of the construction of modern markets on the economy and people’s lifestylesand the second factor is that most affect consumer’s decision to shop in modern market than in the traditionalmarket. In this study, using research method Qualitative Results obtained from this study is the change in theconsumer behavior of society from traditional markets to modern market due to several factors, one of which isthe modern market provides convenient facilities, and women in urban general career that almost did not havetime to shop traditional markets.Keywords: Perilaku Konsumtif, Pasar Tradisional, Pasar Modern